Phonology of Igbo Compound Place Names - Udoye, Ifeoma, Emmanuela (My University, 2019)
This paper presents a phonological study of Igbo language toponyms using Allen’s (1978) Strong Boundary Condition as a theoretical base. The basis of the study is to prove that strong boundary condition for compounds can be applied to Igbo place names in order to further endorse its universality. The paper posits that tonal changes and regressive assimilation are common features among non-productive compounds while productive compounds are insensitive to phonological changes.
Keywords: Phonology; Igbo; Compounds; Place names; Tones